Co‐Producing Resources to Help Improve Access to Primary Care for Young People With Attention Deficit Hyperactivity Disorder - Rebecca Gudka; Anita Salimi; Rachel Gaywood; Dale Hendrick; Kieran Becker; Oliver Medzinskii; Faraz Mughal; G. J. Melendez‐Torres; Jane Smith; Tamsin Newlove‐Delgado; Anna Price (Health Expectations, 2025)
ABSTRACT Background Attention deficit hyperactivity disorder (ADHD) is a common neurodevelopmental disorder resulting in negative long‐term outcomes if untreated. Pathways to healthcare in the United Kingdom are complex, especially for those aged 16–25 transitioning between child and adult mental health services. We aimed to co‐produce evidence‐informed resources to improve accessibility of primary care for young people with ADHD. Methods We utilised co‐production principles from the National Institute for Health and Care Research and findings from recent research to create evidence‐informed resources which collate experiences of multiple stakeholders. Lived experience advisors (young people aged 16–25 with ADHD and their supporters) and healthcare professionals were recruited through previous research engagement and local collaborations. Research partners engaged in workshops or individual meetings to agree priorities, content, and language/visual appearance for outputs. Results Lived experience advisors (7), healthcare professionals (5), and researchers (3) co‐produced a downloadable resource for young people and their supporters. The resource identifies key stages on ADHD healthcare pathways, common barriers, and top tips recommended by people with lived experience, and verified by healthcare professionals. Key messages for primary care professionals were co‐produced. Conclusion Co‐produced resources can help address barriers to accessing ADHD treatment and support via stretched NHS services. Collaborative working also highlighted the need for national policy change to alleviate pressures faced by healthcare professionals and patients. Patient and Public Contribution Two research advisory groups (RAGs) of healthcare professionals and lived experience advisors informed research methods and presentation of results. RAG members participated in co‐production workshops, contributed to authorship, and disseminated outputs.